2019
DOI: 10.1038/s41419-019-1747-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive expression of basic transcription factor 3 predicts poor survival of colorectal cancer patients: possible mechanisms involved

Abstract: Basic transcription factor 3 (BTF3) is associated with the development of several cancers. The aim of our study was to elucidate the role of BTF3 in colorectal cancer (CRC) tissues. CRC tissues or their paired adjacent noncancerous (ANCT) tissues were obtained from 90 patients who underwent operations in our hospital from November 2011 to December 2016, and then we implemented a gene microarray assay for detecting significant changes in gene expression and confirmed expression in tissues using immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Transcriptional and post-transcriptional gene and pathway dysregulation are important cancer signatures in CRC ( Porcellini et al, 2018 ). BTF3, namely, basic transcription factor 3, has been proven to be an oncogene and hazardous prognosticator in CRC ( Liu et al, 2019b ). As a transcription factor, BTF3 is believed to regulate gene expression by binding target promoters, and this mechanism has been reported in breast cancer ( Porcellini et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcriptional and post-transcriptional gene and pathway dysregulation are important cancer signatures in CRC ( Porcellini et al, 2018 ). BTF3, namely, basic transcription factor 3, has been proven to be an oncogene and hazardous prognosticator in CRC ( Liu et al, 2019b ). As a transcription factor, BTF3 is believed to regulate gene expression by binding target promoters, and this mechanism has been reported in breast cancer ( Porcellini et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we refer to this transcription factor characteristic of BTF3 as the transcriptional mechanism, a molecular function primarily occurring in the nucleus. In CRC, the function of BTF3 was first reported to be linked to MAD2L2, MCM3, and PLK1 ( Liu et al, 2019b ). In addition, the alias name of BTF3 is nascent-polypeptide-associated complex beta (NACB).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein is overexpressed in various cancer cell types, including glioma, hepatocarcinoma, pancreatic ductal adenocarcinoma, and colon cancer cells [52]. Recent reports have shown that downregulation of BTF3 attenuates tumorigenesis in colon cancer cells [53,54]. SNAIL1 is a key transcription factor in the early epithelial-to-mesenchymal transition period, the initial and critical timeframe for metastasis [55].…”
Section: Discussionmentioning
confidence: 99%